Prostaglandin E2 and F2α Alter Expression of Select Cholesteryl Esters and Triacylglycerols Produced by Human Meibomian Gland Epithelial Cells. Issue 1 (3rd January 2022) - Ziemanski, Jillian F.; Wilson, Landon; Barnes, Stephen; Nichols, Kelly K.
Abstract : Purpose: PGF2α analogs are commonly used to treat glaucoma and are associated with higher rates of meibomian gland dysfunction (MGD). The purpose of this study was to evaluate the physiological effects of PGF2α and PGE2 on immortalized human meibomian gland epithelial cells (HMGECs). Methods: HMGECs were immunostained for the 4 PGE2 receptors (EP1, EP2, EP3, and EP4) and 1 PGF2α receptor (FP) and imaged. Rosiglitazone-differentiated HMGECs were exposed to PGF2α and PGE2 (10 −9 to 10 −6 M) for 3 hours. Cell viability was assessed by an adenosine triphosphate–based luminescent assay, and lipid extracts were analyzed for cholesteryl esters (CEs), wax esters (WEs), and triacylglycerols (TAGs) by ESI-MSMS ALL in positive ion mode by a Triple TOF 5600 Mass Spectrometer using SCIEX LipidView 1.3. Results: HMGECs expressed 3 PGE2 receptors (EP1, EP2, and EP4) and the 1 PGF2α receptor (FP). Neither PGE2 nor PGF2α showed signs of cytotoxicity at any of the concentrations tested. WEs were not detected from any of the samples, but both CEs and TAGs exhibited a diverse and dynamic profile. PGE2 suppressed select CEs (CE 22:1, CE 26:0, CE 28:1, and CE 30:1). PGF2α dose dependently increased several CEs (CE 20:2, CE 20:1, CE 22:1, and CE 24:0) yet decreased others. Both prostaglandins led to nonspecific TAG remodeling. Conclusions: PGE2 and PGF2α showed minimal effect on HMGEC viability. PGF2α influences lipid expression greater than PGE2 and may do so by interfering with meibocyte differentiation. This work may provide insight into the mechanism of MGD development in patients with glaucoma treated with PGF2α analogs.